2020
DOI: 10.3390/en13092180
|View full text |Cite
|
Sign up to set email alerts
|

AHEAD: Automatic Holistic Energy-Aware Design Methodology for MLP Neural Network Hardware Generation in Proactive BMI Edge Devices

Abstract: The prediction of a high-level cognitive function based on a proactive brain–machine interface (BMI) control edge device is an emerging technology for improving the quality of life for disabled people. However, maintaining the stability of multiunit neural recordings is made difficult by the nonstationary nature of neurons and can affect the overall performance of proactive BMI control. Thus, it requires regular recalibration to retrain a neural network decoder for proactive control. However, retraining may le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Problems related to efficiency in terms of power, performance, and occupied area were also considered and addressed. This approach is in line with another recent example that follows this hardware-oriented strategy (Huang et al, 2020): here an automatic holistic energy-aware design methodology is proposed and applied to a multilayer perceptron designed to be embedded in proactive brain-machine interface edge devices based on FPGA. Another interesting direction for hardware implementation is related to the opensource Neural Network framework called Neural Network on Microcontroller (NNoM) 1 , for implementing (recurrent) neural networks on a microcontroller.…”
Section: Introductionsupporting
confidence: 63%
“…Problems related to efficiency in terms of power, performance, and occupied area were also considered and addressed. This approach is in line with another recent example that follows this hardware-oriented strategy (Huang et al, 2020): here an automatic holistic energy-aware design methodology is proposed and applied to a multilayer perceptron designed to be embedded in proactive brain-machine interface edge devices based on FPGA. Another interesting direction for hardware implementation is related to the opensource Neural Network framework called Neural Network on Microcontroller (NNoM) 1 , for implementing (recurrent) neural networks on a microcontroller.…”
Section: Introductionsupporting
confidence: 63%
“…To evaluate further optimization potential for the energy consumption of the presented type of decoder, we compared our hardware implementation of an adaptable decoder with an optimized implementation of a non-adaptable decoder for an FPGA. We found that the non-adaptable decoder exhibits an energy uptake which is reduced by a factor 2-3 only 25 , such that further optimisation of the FPGA implementation is not expected to yield significant gains.…”
Section: Modular Software Framework and Embedded Hardware Implementat...mentioning
confidence: 92%
“…As a summary, our data-based enhanced control strategy, which is implemented by means of ANNs, allows us to improve a control approach by means of (i) decreasing the design process complexity, and (ii) increasing its scalability [ 14 , 16 ]. The complexity reduction is achieved due to the fact that ANNs do not require a such precise adjustment to the scenario as usual filtering strategies do.…”
Section: Data-based Enhanced Control Strategymentioning
confidence: 99%
“…Data-driven methods and ANNs have arisen as new approaches able to offer a good control performance at the same time they increase the scalability and decoupling of the control strategy from the highly complex mathematical models [ 14 , 15 , 16 , 17 , 18 , 19 ]. In such a context, ANNs have been considered to perform different tasks: (i) act as soft-sensors, (ii) complement the model-based controllers, and (iii) act as a control strategy as such.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation